New Zealand : Financial Sector Assessment Program: Detailed Assessment of Observance-Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of Observance of the Basel Core Principles for Effective Banking Supervision (BCP) in New Zealand. The supervisory approach of the Reserve Bank of New Zealand (RBNZ) reflects the characteristics of the local banking industry and the authorities' goal to limit moral hazard by relying on market discipline and not offering deposit insurance. Banks offer traditional products in a highly concentrated market. Since the most recent Financial Sector Assessment Program, the RBNZ has increased attention to strengthening regulatory discipline. The current approach to supervision is limited by the heavy weight the RBNZ places on market discipline compared with regulatory discipline. Better compliance with the BCP and enhanced effectiveness of the RBNZ three-pillar approach are recommended.